Analisis Dampak Pengembangan Pariwisata Berkelanjutan di Kota Singkawang - Sofiani Sofiani; Candy Maqdalene (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Geographically, Singkawang is classified as a relatively open area, especially the coastal areas, which are the fastest to change. With the improvement of transportation facilities and infrastructure, relations between community groups are increasingly intensive and they are increasingly mixing. The purpose of this study is to explore more deeply the potential for sustainable tourism development in Singkawang City which has its own uniqueness and characteristics. Then for the research method used is a qualitative method by making several reliable sources as informants and analyzing from various perspectives. The results of the study indicate that the 4A components in Singkawang City have generally been running well in increasing the interest of tourists to return. In terms of Attraction, there are new tourist attractions that have emerged. Tourist villages are also built and made as one of the tourist attractions, so that tourist attractions in the city of Singkawang are not monotonous and have many choices. Some of the tourist villages in the city of Singkawang are Batu Belimbing tourist villages, Binuo Garantukng are several tourist villages that are not too far from the city of Singkawang, around 5-7 km and have very beautiful natural potential. This is a special attraction for tourists to return to the city of Singkawang.